Bioreceptive design: a novel approach to biodigital materiality. Issue 1 (20th July 2016) - Cruz, Marcos; Beckett, Richard
Abstract : Today, at a time of unprecedented urban development, there is urgency to improve the environmental quality of cities. The present 'greening' of urban spaces is an ongoing response to a dirty industrial past and present, with a drive to transform cities to have better air and water, more tree-lined streets and open parks. But the amount of urban public green space varies massively between cities around the world and increasing this, or designing for it, is a particular challenge where there is pressure for space, resources, and development. The architectural fabric itself – building envelopes, roofs, and façades – has been targeted as an opportunity for additional greening. A number of strategies integrating vegetation and other photosynthetic systems onto buildings have been developed, which provide passive climatic control as well as aiding storm-water management and creating new ecological habitat, in addition to lowering atmospheric CO2 . However, 'green walls', where plants and foliage are grown on the sides of buildings as a kind of secondary skin, have been less successful and have proven expensive to implement. Maintenance costs are significant due to the need to overcome gravity, primarily through mechanical irrigation.